The Role of Guidance Counselors in Supporting the Emotional Well-being of Children with Special Needs at SKH Negeri 2 Lebak - Suci Nabillah; Yahdinil Firdha Nadirah (Psikologi Prima, 2025)
This study aims todescribe the role of guidance counselors in supporting the emotional well-being of childrenwith special needs at SKHN 2 Lebak. This study uses qualitative research with a case study approach, with the research subjects being guidance counselors represented by special assistant teachers or homeroom teachers. Data collection was carried out through observation, interviews, and documentation. The data analysis techniques used were data reduction, data display, and conclusion drawing.The researcher used triangulation of sources to obtain data validity. Based on the study, it can be concluded that the role of guidance counselors in supporting the emotional well-being of children with special needs at SKHN 2 Lebak includes several important functions, namely as a source of information, a source of guidance, a source of support, and a source of guidance.The researcher used triangulation of sources to obtain data validity. Based on the study, it can be concluded that the role of guidance counselors in supporting the emotional well-being of children with special needs at SKHN 2 Lebak includes several important functions, namely as a source of information, a source of guidance, a source of support, and a source of guidance.The researcher used triangulation of sources to obtaindata validity. Based on the research, it can be concluded that the role of guidance counselorsin supporting the emotional well-being of children with special needs at SKHN 2Lebak includes several important functions, namely as communicators, facilitators,motivators, and advisors who help children manage their emotions and fostergood social relationships. In addition, guidance counselors also collaborate with homeroom teachers and parents to create an environment that supports the emotional developmentof children with special needs. The strategies implemented includestructured guidance and the use of appropriate techniques to helpchildren manage their emotions and improve their overall psychosocial well-being.